Photochemical aging of aviation emissions: transformation of chemical and physical properties of exhaust emissions from a laboratory-scale jet engine combustion chamber - A. Hartikainen; M. Ihalainen; D. Shukla; D. Shukla; M. Rohkamp; A. Mukherjee; Q. He; S. Piel; S. Piel; A. Virkkula; D. Li; T. Kokkola; et al. (Atmospheric Chemistry and Physics)
Aviation is an important source of urban air pollution, but the impacts of photochemical processing on the exhaust emissions remain insufficiently characterized. Here, the physical–chemical properties of fresh and photochemically aged emissions from a laboratory-scale jet engine burner operated with JP-8 kerosene were studied in detail with a range of online and offline methods. The fresh emissions contained high amounts of organic matter present predominantly in the gaseous phase. Photochemical aging in an oxidation flow reactor caused substantial formation of oxidized organic aerosol, increasing the particle mass approximately 300-fold. During aging, aromatic hydrocarbons and alkanes in the gas-phase decayed, while gas-phase oxidation products, such as small carbonyls and oxygenated aromatics, increased. The composition of organic matter became more complex by photochemical processing, with the average particulate carbon oxidation state increasingly growing throughout the addressed exposure range (equivalent to 0.2 to 7 d in the atmosphere) with a ΔH:C/ΔO:C<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="72pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="0a5fddb200c21a75edc2d7a8feaec4b6"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-9275-2025-ie00001.svg" width="72pt" height="14pt" src="acp-25-9275-2025-ie00001.png"/></svg:svg> slope of −0.54. Simultaneously, the near-UV wavelength absorption by the particles increased due to enhanced particulate mass. The imaginary refractory indices of organic particulate matter were 0.0071 and 0.00013 at the wavelength of 520 nm for the fresh and photochemically processed particles, respectively, indicating secondary production of weakly absorbing brown carbon. The direct radiative forcing by the exhaust particles was estimated by a Mie model, which revealed a prominent shift from a warming to cooling climate effect upon photochemical aging. The results highlight the importance of considering secondary aerosol formation when assessing the environmental impacts of aviation.